Training on making Interesting Percentage Learning Media Using Canva - Besse Qur’ani; Nurhijrah; Syarifa Suryana; Israwati Hamsar (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose Presentation of learning media that is interesting, creative, and informative is one of the capitals for creating lessons that are easily accepted by students. The purpose of community service is creativity and the creation of innovation, especially in making learning media, especially in percentage broadcast media. Methode - The method used is demonstration by practicing directly through the Zoom Meeting. The material provided includes creating an account, introducing features, using available templates to managing the use of existing elements to support the material that will be made into slides. Result and discussions - Community service activities are carried out through the delivery of material including creating accounts, introducing features, using available templates to setting up the use of existing elements to support material that will be made into slides. Conclusion - This training can add insight and knowledge to students, especially in adding references to how to deliver teaching materials, attractive percentages.